The Association of Perceived Neighborhood Environment Factors and Methamphetamine Use among Drug Addicts in Northern, Thailand. (Indian Journal of Public Health Research & Development, 2020)
Background: Neighborhood environment factors influence health-related behavior, including substance use.Many researches have focused on the effect of neighborhood factors with drug use in general population;a few studies have focused on vulnerable group like drug addicts. This study aimed to investigate theassociation between neighborhood environment factors and methamphetamine use among drug addicts.Method: This cross-sectional study was conducted among 364 drug addicts at drug treatment center inNorthern Thailand. The data collection by using structured interview, including substance use and perceivedneighborhood environment, which conducted by standardized interviewers. Multivariate logistic regressionwas applied to interpret the neighborhood environment factors related with methamphetamine use.Results: The results revealed that most of respondents (65.4%) used methamphetamine and 34.6% usedother illicit drugs. The greater of perceived neighborhood crime (adjusted OR= 2.99, 95% CI: 1.64, 5.49)and stigma of addiction (adjusted OR= 2.23, 95% CI: 1.23, 4.05) were associated with increased risk ofmethamphetamine use. Drug addicts who were male, unemployed and had peers or family used drug weremore likely to use methamphetamine.Conclusions: The neighborhood factors influence methamphetamine use. Thus, the better understandingof neighborhood context is important to developing prevention and intervention to reduce substance use.health-related behavior.
Keywords: Methamphetamine; Crime; Neighborhood; Thailand.